IMPLEMENTATION OF THE RICE FARMING BUSINESS INSURANCE PROGRAM (AUTP) IN JUNJUNG SIRIH DISTRICT, SOLOK REGENCY: IMPLEMENTASI PROGRAM ASURANSI USAHA TANI PADI (AUTP) DI KECAMATAN JUNJUNG SIRIH KABUPATEN SOLOK - Luthfi Fakhruzi; Rizki Syafril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research was conducted using a qualitative approach with a descriptive method, in determining the researcher's informants using purposive sampling methods and techniques. Data collection techniques are carried out by interviews, observations, and documentation. In testing the validity of the data, the researcher used the triangulation method. Meanwhile, the data analysis technique uses data reduction, data presentation, and conclusion. The results of the study show that although this program has great potential to support farmers, several challenges such as limited resources, lack of understanding of farmers, and suboptimal coordination between implementing parties are still obstacles. To increase the effectiveness of the program, it is recommended that there be increased socialization, training for implementers, and strengthening coordination between all related parties. In addition, there is a need for policies that are more responsive to the social and economic conditions of farmers so that this program can provide maximum benefits. Thus, it is hoped that the AUTP program can continue to develop and have a significant positive impact on farmers in Junjung Sirih District, Solok Regency.